2018
DOI: 10.1002/ijc.31821
|View full text |Cite
|
Sign up to set email alerts
|

Circulating inflammatory markers and colorectal cancer risk: A prospective case‐cohort study in Japan

Abstract: Blood levels of inflammation-related markers may reveal molecular pathways contributing to carcinogenesis. To date, prospective associations with colorectal cancer (CRC) risk have been based on few studies with limited sets of analytes. We conducted a case-cohort study within the Japan Public Health Center-based Prospective Study Cohort II, comparing 457 incident CRC cases during median 18 years follow-up with a random subcohort of 774 individuals. Baseline plasma levels of 62 cytokines, soluble receptors, acu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 42 publications
2
23
0
Order By: Relevance
“…Multiplex assay platforms are increasingly used to examine associations of inflammation‐related biomarkers with cancer risk . Previous studies of ESCC risk and these biomarkers are limited in number and sample size.…”
Section: Introductionmentioning
confidence: 99%
“…Multiplex assay platforms are increasingly used to examine associations of inflammation‐related biomarkers with cancer risk . Previous studies of ESCC risk and these biomarkers are limited in number and sample size.…”
Section: Introductionmentioning
confidence: 99%
“…Future studies will be required to evaluate the inflammatory response across racially divergent breast cancer cell lines or tissues. What we do know, however, is that compounds like apigenin that attenuate the CCL2/CCR2 axis would slow the aggressive nature of TNBC and hormone positive breast cancers (27,28) by attenuating invasion, metastasis, EMT and the development of drug resistance (59)(60)(61)(62). CCL2 inhibitors have been tested in various tumors, tumor cells and xenograft models with CCL2 lowering effects brought about by losartan (63) anlotinib (64) imatinib (65) zoledronic acid (66) oroxylin A (67) aspirin (68) natural compounds in coffee (kahweol acetate, cafestol) (69) or conophylline from Ervatamia microphylla (70) which can reduce invasive inflammatory tumor infiltration.…”
Section: Discussionmentioning
confidence: 99%
“…What is evidently a critical situation is that these inflammatory proteins, in particular, the CCL2 and IL-6 are brought about by the actual cancer treatments themselves (e.g., radiotherapy (16) chemotherapy (8), which in turn are then associated with tumor recurrence (17) and chemo-resistance (18,19), Inflammatory events in general, whether it be from other parts of the body such as the liver (9,20) adipose tissue in obesity or arising from viral origin tend to elevate TNF-a, IL -6 and CCL2 then becoming risk factors for the development of diverse cancers (21) aggressive tumors with advanced stage tumor grade and greater rates of mortality (22,23). Meanwhile, it is believed that drugs or natural compounds that can attenuate CCL2 and IL-6 would slow the aggressive nature of advanced cancers (24)(25)(26) to the inclusion of triple negative breast cancer (TNBC) and hormone positive breast cancers (27,28). It is believed that utilizing synthetic or natural small molecules as CCR2 inhibitors (CCR2i) can increase overall survival odds (29,30).…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, the emphasis has been on prevention of CRC development and regular screening to detect and cure such cancer at an early stage. CRC development is also associated with chronic inflammation and high levels of circulating inflammatory biomarkers [5,6]. Recent reports have shown that inflammation induced by certain types of diet and alterations in the microbiome is associated with increased risk of CRC development in men and women [7,8].…”
Section: Introductionmentioning
confidence: 99%